Analisis Ekonomi Neo-Klasik terhadap Pertumbuhan Ekonomi Kabupaten Deli Serdang (International Forum of Researchers and Lecturers, 2025)
Deli Serdang Regency located in North Sumatra Province has significant economic potential, supported by the agriculture, industry, trade, and service sectors. In recent years, Deli Serdang Regency has experienced fluctuations in its economic growth. This study analyzes the economic growth of Deli Serdang Regency using the Solow-Swan model. Secondary data from the Central Statistics Agency (BPS) in 2019-2020 accessed through the website https://www.bps.go.id/id analyzed to estimate model parameters. The results show that: (1) the level of savings and investment has a significant effect on economic growth, (2) technology and labor growth play an important role in increasing productivity, and (3) fiscal and monetary policies need to be optimized to increase economic growth. The Solow-Swan model effectively explains the dynamics of economic growth in Deli Serdang Regency.